Reproductive behaviour and consistent patterns of abnormality in offspring of Vietnam veterans. Issue 12 (December 1988) - Field, B; Kerr, C
Abstract : In view of the persistent claim of Australian Vietnam veterans that their health and that of their children were adversely affected, aspects of reproductive behaviour and the distribution of disease and disability in family units were investigated in a sample of Tasmanian veterans and another group chosen for comparison of selected characteristics. One third of veterans reported serious health problems and their reproductive behaviour differed with more marital breakdowns, increased use of reproductive alternatives, and more complications of pregnancy. Patterns of malformation and disease among veterans' children involved predominantly the central nervous, skeletal, and cardiovascular systems. A similar pattern was detected on review of the three other major investigations on veterans' offspring in the USA and Australia. Although plausible mechanisms remain unknown, the evidence from all available studies supports a causal contribution to defects in veterans' children from a paternally mediated genetic effect.